Optical Crosstalk in WDM Fiber-Radio Networks - Rambabu, K.; ., . (International Journal of Engineering and Technology, 2018)
This paper investigates the impact of optical crosstalk in fiber-radio systems incorporating wavelength division multiplexing, (WDM). We present a simple analytical model that allows the impact of optical crosstalk in such networks to be assessed and validate band optical crosstalk. We show that crosstalk-induced power penalties in fiber-radio WDM networks. In addition, in contrast to baseband modulated optical links, the crosstalk channel in fiber-radio systems can be filtered electrically if the crosstalk signal carries a different wireless frequency. However, a power penalty is still observed for the case of in-band crosstalk, even for perfect electrical filtering of the crosstalk channel.Â Â